2021
DOI: 10.3390/molecules26041073
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Strategy for Fabrication Lysozyme-Loaded Mesoporous Silica Nanotubes from Electrospun Silk Fibroin Nanofiber Templates

Abstract: This paper presents a facile and low-cost strategy for fabrication lysozyme-loaded mesoporous silica nanotubes (MSNTs) by using silk fibroin (SF) nanofiber templates. The “top-down method” was adopted to dissolve degummed silk in CaCl2/ formic acid (FA) solvent, and the solution containing SF nanofibrils was used for electrospinning to prepare SF nanofiber templates. As SF contains a large number of -OH, -NH2 and -COOH groups, the silica layer could be easily formed on its surface by the Söber sol-gel method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…[ 30 ] The degummed fibroin retains the structure of its large filamentous fibers and is commonly dissolved in a lithium bromide solution or a calcium chloride/ethanol/water ternary solvent. [ 31 ] The dissolved SF is then eliminated from the salt solution by dialysis to form a regenerated SF aqueous solution. [ 32 ] Some studies have directly prepared tissue engineering scaffolds utilizing SF aqueous solution.…”
Section: Characteristics Of Silk Fibroinmentioning
confidence: 99%
“…[ 30 ] The degummed fibroin retains the structure of its large filamentous fibers and is commonly dissolved in a lithium bromide solution or a calcium chloride/ethanol/water ternary solvent. [ 31 ] The dissolved SF is then eliminated from the salt solution by dialysis to form a regenerated SF aqueous solution. [ 32 ] Some studies have directly prepared tissue engineering scaffolds utilizing SF aqueous solution.…”
Section: Characteristics Of Silk Fibroinmentioning
confidence: 99%
“…Zhu et al reported a facile strategy for lysozyme immobilization and delivery using mesoporous silica nanotubes from electrospun silk fibroin nanofiber templates. [36] They obtained mesoporous silica nanotubes with inner diameters about 200 nm and wall thickness ranged from 37 � 2 nm to 66 � 3 nm, which achieved a high lysozyme loading (up to 31.82%) and long-term sustained release for 15 days. Wang et al used dendritic mesoporous silica nanoparticles for lysozyme delivery and studied the relationship between the particle size/pore size and antibacterial activity of the delivered enzyme.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…Zhu et al. reported a facile strategy for lysozyme immobilization and delivery using mesoporous silica nanotubes from electrospun silk fibroin nanofiber templates [36] . They obtained mesoporous silica nanotubes with inner diameters about 200 nm and wall thickness ranged from 37±2 nm to 66±3 nm, which achieved a high lysozyme loading (up to 31.82%) and long‐term sustained release for 15 days.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…SBS, however, presents some limits in regard to drugs encapsulation within nanofibers. In particular, during nanofibers production, liquid and solid drugs both emerge on the fibers surface due to the high evaporation rate of the solvent during the process [ 24 , 26 ], thus preventing the possibility of slowing down the release kinetics and obtaining a sustained release over time [ 27 , 28 , 29 ]. Considering that the correct encapsulation of liquid and solid drugs is crucial for achieving their controlled release, but also that appropriate production time and cost are essential for industrial scalability, it could be an interesting challenge to evaluate the existing difference, to form the production to the application, of the same drug delivery systems produced for ES or SBS.…”
Section: Introductionmentioning
confidence: 99%